ishlahseilla, Metode Pembelajaran Numbered Together Dalam Pengembangan Kurikulum Merdeka Terhadap Siswa Kelas X SMK Muhammadiyah Bulakamba.docx - Seillariski, Ishlah; Askanah, Aas (EDUCATIVA, 2023)
The influence of the times that greatly impacts the values of life brings agent changes to the situation and conditions in the future. where it becomes a worldwide life factor in the scope of education itself. cultural acculturation, ethnic differences, and religious differences that trigger issues and solutions in education, economics, and multiculturalism. The changes that exist in this context, education plays an important role in the goals stated in the 1945 Constitution in the 4th paragraph, namely to educate the nation's life. Therefore, in a lesson, there is a need for methods, learning media for curriculum development that has been set. Learning methods are a certain way to do learning design, where the numbered head together method is the main goal in developing this research. This has a major effect on the efficiency of learning. The purpose of this research is to develop the potential of students with the development of an independent curriculum. This research is a study that uses a qualitative approach to social phenomenology, the data collected comes from interviews of various sources, review of library materials, and interviews of various sources in the form of: books, articles, scientific works and encyclopedias that are often published in mass media such as newspapers, scientific journals, and magazines as well as research conducted by going directly to the field without going through the information media to obtain the results of developing an independent curriculum in the learning process using the Numbered Head Together learning method.